Examining Emancipated Curriculum Development in Middle Schools: A Case Study - Kapitariyani Kimpo Ellen; Lala Bumela Sudimantara (PANYONARA: Journal of English Education, 2023)
Indonesia’s education system has been facing a significant learning crisis, as evidenced by the country’s declining scores in the 2018 PISA results and its expected drop in the English Proficiency Index ranking in 2022. To tackle this challenge, Indonesia has introduced an Emancipated Curriculum that aims to transform learning in the country. The Emancipated Curriculum is designed to be student-centered, differentiated learning, project-based learning, exploratory learning, and holistic learning. This study discusses the discussion of the Kurikulum Merdeka, school perceptions about the meaning of the Independent Curriculum, implementation in secondary schools. This research uses qualitative research with a case study method. The data in this research was obtained from interviews and documents. The findings show that teachers plan the curriculum with a focus on critical and creative thinking, develop their own learning materials to enhance students’ cognitive abilities, and make changes to syllabi and lesson plans. However, the study also reveals that the learning media being developed is not yet digital, which may hinder the effective implementation of the Emancipated Curriculum. Furthermore, traditional learning approaches still dominate the assessment and learning processes. Overall, this study sheds light on the development of the Emancipated Curriculum and highlights the need for further research in this area.